2017
DOI: 10.1038/srep41410
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of polyclonal infection and heteroresistance on treatment of tuberculosis patients

Abstract: Mixed strain infections of Mycobacterium tuberculosis make diagnosis, treatment, and control of tuberculosis (TB) more difficult. This study was aimed to evaluate the relationship between mixed infections, antibiotic resistance patterns and treatment of TB patients. In this study, among 2850 suspected TB clinical samples, a total of ninety-six clinical samples from 66 TB confirmed patients were subjected to the 24-locus variable-number tandem repeat method to evaluate the prevalence of mixed infections. For al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…On the other hand, molecular assays may not be sensitive enough to detect drug-resistant subpopulations (heteroresistance) at the critical 1% proportion level (10% for PZA) defining clinical resistance (17,18,23). The magnitude of mixed and polyclonal infections among TB patients is relatively unknown, although recent studies clearly showed that heteroresistance occurs frequently (ϳ20% to 45%) in specific TB populations and that it may also have a negative impact on the treatment outcome (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, molecular assays may not be sensitive enough to detect drug-resistant subpopulations (heteroresistance) at the critical 1% proportion level (10% for PZA) defining clinical resistance (17,18,23). The magnitude of mixed and polyclonal infections among TB patients is relatively unknown, although recent studies clearly showed that heteroresistance occurs frequently (ϳ20% to 45%) in specific TB populations and that it may also have a negative impact on the treatment outcome (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…The sub-culturing of isolates for MB7H10 and MYCTB plate DST may have caused changes in the sample strain population from the original sample used for DST in presence of hetero-resistance [ 18 ]. Studies have indicated hero-resistance to affect DST results from the sub-cultured strains [ 19 , 20 ], however, this is expected to be minimal given the low prevalence of hetero-resistance. This is one of the few studies which have compared LJ and MB7H10 DST with MYCOTB plate and our findings are vital for future studies and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies have shown that the rate of polyclonal infections in clinical specimens is more than 50 percent in our region [ 9 11 ]. With this background, Spoligotyping was performed on clinical specimens and their respective cultures, and interesting results were obtained.…”
Section: Main Textmentioning
confidence: 99%
“…MIRU-VNTR is the best and most widely used method for identifying mixed infections in TB [ 8 ]. Several studies have used MIRU-VNTR to diagnose mixed infections in clinical specimens and this method has been successful in detecting the mixed infections [ 9 11 ]. But a recent article suggests that mixed infections in clinical specimens can disrupt direct genotyping and challenge the Spoligotyping technique [ 3 ].…”
Section: Introductionmentioning
confidence: 99%